The Influence of Work-Life Balance and Burnout on Nurse Performance: The Mediating Role of Job Satisfaction - Insan Kamil Wahyudi; Deswarta Deswarta (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to determine the effect of work-life balance and burnout on nurse performance, with job satisfaction serving as a mediating variable, at Petala Bumi General Hospital. The sample consists of nurses from Petala Bumi General Hospital. The population for this study was 105 nurses, and using the Slovin Formula, a sample of 52 nurses was selected. Data collection was conducted by distributing questionnaires directly to the subjects at Petala Bumi General Hospital. The types and sources of data include primary and secondary data, collected through observation, questionnaires, interviews, and literature reviews. The data analysis technique employed in this study is multiple linear regression, performed using SmartPLS version 4. The results indicate that work-life balance and burnout significantly affect nurse performance, with job satisfaction acting as a mediating variable.